Design and development of BLUECARV: A remotely operated underwater vehicle for blue carbon monitoring and marine ecosystem conservation - Widiarti, Yuning; Sukaridhoto, Sritrusta; Sutrisno, Imam; Budianto, Budianto; Rahmat, Mohammad Basuki (Edelweiss Applied Science and Technology, 2026)
Blue carbon ecosystems such as mangroves, seagrasses, and coral reefs require frequent and accurate monitoring, yet traditional diver-based surveys are limited by depth, cost, and operational risks. This study aims to develop BLUECARV, a low-cost and modular Remotely Operated Vehicle (ROV) designed to enhance ecological observation and environmental data acquisition in coastal habitats up to 100 meters depth. The system integrates a 3-axis manipulator arm, multi-parameter environmental sensors (temperature, salinity, pH, and pressure), and an Ultra HD underwater camera within a hybrid modular architecture that supports flexible payload configurations. BLUECARV was fabricated using corrosion-resistant materials and evaluated through laboratory and field tests, with performance metrics including maneuverability, sensor accuracy, latency, and depth-holding capability. The results show stable six-degree-of-freedom maneuvering, ±0.1 m depth stability, sensor deviations below ±1%, and video latency under 150 ms, while the manipulator achieved a 95% object-handling success rate. These findings demonstrate that BLUECARV provides reliable visual and environmental data for blue carbon ecosystem monitoring. Its affordability, modularity, and operational stability offer practical benefits for long-term coastal habitat assessment, biodiversity surveys, and community-level conservation, while enabling future upgrades such as AI-based navigation and advanced monitoring sensors.